Natural fibers as reinforcement additives for geopolymers – A review of potential eco-friendly applications to the construction industry - Silva, Guido (2020)
The construction industry is responsible not only for the consumption of huge amounts of natural resources but also for the emission of large quantities of CO2. Geopolymers have emerged as an environmentally friendly alternative for conventional construction materials since they can be produced from industrial wastes. Similarly to ordinary concrete, geopolymers can also improve their mechanical properties when reinforced with fibers. This paper presents a review of recent advances in the production of natural fiber-reinforced geopolymers produced from industrial by-products and waste materials as promising sustainable construction materials. Regarding the use of industrial wastes, this paper reports the use of fly ash, ground granulated blast furnace slag, construction and demolition wastes and mine tailings for the production of high strength geopolymers. At the same time, a survey of successful reinforcement with natural fibers (from plants such as pineapple leaf, sisal, linen, flax, sweet sorghum, and cotton) is also reported. In this respect, it has been found that the type of fiber, dimensions, amount and pretreatment of fibers affect the final properties of the resulting composites. Moreover, layer reinforcement using woven and non-woven layers of natural fibers seem to be more effective than short fibers randomly oriented.